2017
DOI: 10.4067/s0718-95162017005000015
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing NO3- supply confers NaCl tolerance by adjusting Cl- uptake and transport in G. max & G. soja

Abstract: The objective of this work was to elucidate NO 3 -supply, Cl -toxicity, and Cl -/NO 3 -interaction in Glycine max and Glycine soja under salt stress. G. max cultivars (Lee68 and Jackson) and G. soja accessions (BB52 and N23227) with different salt tolerance were chosen as the experimental materials. Effects of low (0.75 mmol/L), normal (7.5 mmol/L), and high (15

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Furthermore, the intensified Na + absorption interferes the ionic balance and predominantly restrains K + uptake due to the similar ionic diameter of two ions and, hence, disrupts membrane-anchored carriers actions and prevents many enzymes to be metabolically active and dynamic (Apse and Blumwald 2002). Moreover, under NaCl salinity, Na + partially substitutes Ca 2+ in cell walls, interferes the cell function, and affects plant yield and productivity, causing ionic imbalances or deficiency of nutrients (Farhodi 2011;Guo et al 2017). Cell membrane damage under salinity stress and the subsequent malondialdehyde production followed by cell membrane lipid components breakdown are reliable biomarkers to assay the plant responses to salinity stress (Farhodi 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the intensified Na + absorption interferes the ionic balance and predominantly restrains K + uptake due to the similar ionic diameter of two ions and, hence, disrupts membrane-anchored carriers actions and prevents many enzymes to be metabolically active and dynamic (Apse and Blumwald 2002). Moreover, under NaCl salinity, Na + partially substitutes Ca 2+ in cell walls, interferes the cell function, and affects plant yield and productivity, causing ionic imbalances or deficiency of nutrients (Farhodi 2011;Guo et al 2017). Cell membrane damage under salinity stress and the subsequent malondialdehyde production followed by cell membrane lipid components breakdown are reliable biomarkers to assay the plant responses to salinity stress (Farhodi 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this inhibition is overcome when plants are not provided a nitrate pretreatment (Glass and Siddiqi, 1985). In another example, nitrate has been shown to be an effective competitor of chloride uptake in soybean (Glycine max), providing a possible mechanism that could be used to alleviate chloride toxicities (Guo et al, 2017). Dhugga et al (1988) demonstrated that both nitrate and chloride uptake into excised maize roots can be inhibited by phenylglyoxal.…”
Section: Functional Roles Of Npf64 and Npf66 In Maize Nutrient Tranmentioning
confidence: 99%
“…from being outcompeted in the rhizosphere (Guo et al, 2017). Many PGPM genera, such as Bacillus, Streptomyces, and Pseudomonas, can alleviate salt stress in soils through a variety of other mechanisms; however, this has not been investigated in aquaponic solution (Dodd and Pérez-Alfocea, 2012;Egamberdieva et al, 2019).…”
Section: Introductionmentioning
confidence: 99%